A SOCIODEMOGRAPHIC STUDY OF SUICIDAL DEATHS (Journal of Forensic Medicine & Toxicology, 2014)
Suicide is a major public health problem and reflects the social and mental well being of a society. The study conducted between January 2011 and April 2012 includes 40 cases of suicides. It was observed that the maximum number of cases were in the age group of 20 to 30 years (50 %) and the male: female ratio was 2.07:1. A majority of the cases were from the urban areas and hanging was found to be the commonest method for suicide. The reasons for suicide were family problems, love disappointments, failure in studies, chronic illness, etc. Only 7.5% of the cases had past history of attempt to commit suicide.
Keywords: Suicide; risk factors of suicide; method of suicide